Family recognition of celiac disease - Szałowska, Dorota; Bąk-Romaniszyn, Leokadia (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Celiac disease is a permanent intolerance to gluten that leads to small-bowel mucosal villous atrophy during autoimmune processes in genetically predisposed individuals. At present the diagnosis of celiac disease is based on characteristic clinical symptoms, the results of serological investigations (tissue transglutaminase ten times the upper limit of normal, presence of antiendomysial antibodies – EMA) and positive results of genetic examinations. The aim of this study is to present a medical history of a family in which the mother and younger son were diagnosed with celiac disease (confirmed by genotype examination). Before the genetic examination, the father and the elder son were also suspected of suffering from this disease (they were on gluten-free diets). The authors emphasize the usefulness of HLA-DQ2/DQ8 determination in first-degree relatives of celiac patients.